2015
DOI: 10.1007/s11356-015-5423-5
|View full text |Cite
|
Sign up to set email alerts
|

Root water transport of Helianthus annuus L. under iron oxide nanoparticle exposure

Abstract: The application of nanomaterials in commercially available products is increasing rapidly for agriculture, phytoremediation and biotechnology. Since plants suppose the first sink for the accumulation of nanoparticles from the environment, emerging studies have focused on the general consequences for plants and their effects on the biomass production. However, effects on the root surface, as well as blockage of nutrients and water uptake by the roots, may also occur. This experiment was designed to prove if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(63 citation statements)
references
References 65 publications
4
52
1
Order By: Relevance
“…Iron oxides and their aggregates cling to the negatively charge cell surface due to electrostatic adhesion [34]. This blocking effect of NPs inhibits sufficient water uptake [37]. According to the literature, most plants accumulate heavy metals in roots [19].…”
Section: Resultsmentioning
confidence: 99%
“…Iron oxides and their aggregates cling to the negatively charge cell surface due to electrostatic adhesion [34]. This blocking effect of NPs inhibits sufficient water uptake [37]. According to the literature, most plants accumulate heavy metals in roots [19].…”
Section: Resultsmentioning
confidence: 99%
“… 47 Due to phytotoxicity, plant growth may be slow, decrease in plant hormones, change in transcriptional genes profile and decreased photosynthetic rate had been observed. 48 - 50 Yusefi-Tanha et al 51 found that small sized CuO nanoparticles (25 nm diameter) were more phytotoxic than large sized CuO nanoparticles (50 nm and 250 nm) to Soybean. Moreno-Olivas et al 52 reported that nanoparticles interaction with plant cell could lead to change in plant genes expression.…”
Section: Discussionmentioning
confidence: 99%
“…Boron reduction could be due to the immobilization of this element in the medium by the adsorption capacities of NPs. 41 There is insufficient information to understand how AgNPs affect nutrient absorption. Zuverza-Mena et al 37 suggest that it is possible that AgNPs physically block the diffusion pathway or the channels for active absorption.…”
Section: Discussionmentioning
confidence: 99%